2019
DOI: 10.1287/mnsc.2017.2944
|View full text |Cite
|
Sign up to set email alerts
|

Motivating User-Generated Content with Performance Feedback: Evidence from Randomized Field Experiments

Abstract: We design a series of online performance feedback interventions that aim to motivate the production of user-generated content (UGC). Drawing on social value orientation (SVO) theory, we develop a novel set of alternative feedback message framings, aligned with cooperation (e.g., your content benefited others), individualism (e.g., your content was of high quality), and competition (e.g., your content was better than others). We hypothesize how gender (a proxy for SVO) moderates response to each framing, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(27 citation statements)
references
References 78 publications
0
26
1
Order By: Relevance
“…The number of page views (attention) had a negative effect on volunteers' likelihood to accept additional consultations; this finding is different from past research [18]. There are two plausible explanations for this.…”
Section: Discussion Limitation and Conclusioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The number of page views (attention) had a negative effect on volunteers' likelihood to accept additional consultations; this finding is different from past research [18]. There are two plausible explanations for this.…”
Section: Discussion Limitation and Conclusioncontrasting
confidence: 85%
“…Previous studies have identified several factors that affect participation in voluntary behaviors, with effortbased feedback receiving much attention [18,20,29]. We focus on two technological manifestations of feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to understand individual's self-presentation of prosocial behavior. The existing literature in user content generation has covered many motivators including financial incentive, social norms, collectivism, individualism, and social comparison to encourage content generation [5,12,13]. To the best of our knowledge, no prior work has considered the negative consequence of content generation.…”
Section: Discussionmentioning
confidence: 99%
“…Huang, Chen [13] conducted a field experiment to find that users' social sharing is encouraged by monetary incentive as well as relational and cognitive capital framings. Huang, Burtch [12] studied novel message framings based on performance feedback and disentangled the moderation role of gender. Our study differs from these works by directly looking at the likability of different framings from an audience perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More generally, the paper belongs to the literature that analyzes what drives contributions to user-generated content. 3 The topics addressed in the prior related literature include the role of personal gain (Shah, 2006), group size (Zhang and Zhu, 2011), networks (Fershtman and Gandal, 2011;Ransbotham, Kane, and Lurie, 2012), spillovers (Kummer, 2014), symbolic awards (Gallus, 2017), performance feedback (Huang, Burtch, Gu, Hong, Liang, Wang, Fu, and Yang, 2018), monetary rewards vs social motives (Sun, Dong, and McIntyre, 2017), contributor diversity (Ren, Chen, and Riedl, 2015), and economic conditions, such as unemployment (Kummer, Slivko, and Zhang, 2015) and migration (Slivko, 2018). More closely related to our work is Kane and Ransbotham (2016) who study the relationship between contributions and consumption of content.…”
Section: Introductionmentioning
confidence: 99%